2001
DOI: 10.1007/s00268-001-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgical excision of rectal tumors: Indications and results

Abstract: Transanal endoscopic microsurgery (TEM) allows local excision of rectal tumors located 4 to 18 cm above the anal verge. The technique is not yet generally established because of the necessary special instrumentation and tools, the unusual technical aspects of the approach, and the stringent patient selection criteria. The aim of this prospective, descriptive study was to analyze the currently accepted indications for TEM and to evaluate the use of this procedure for treating rectal cancer. Over a 4-year period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
13

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(65 citation statements)
references
References 50 publications
2
49
1
13
Order By: Relevance
“…Other studies have also demonstrated good results with low recurrence and high survival for selected pT1N0 rectal adenocarcinomas treated by TEM alone 2,4,8,13,20,21,36 . In the advent that pathological examination reveals a pT1 lesion with unfavorable features or a more advanced lesion the authors recommend complementary treatment with radical surgery and/or CMT.…”
Section: Early Rectal Cancersmentioning
confidence: 87%
“…Other studies have also demonstrated good results with low recurrence and high survival for selected pT1N0 rectal adenocarcinomas treated by TEM alone 2,4,8,13,20,21,36 . In the advent that pathological examination reveals a pT1 lesion with unfavorable features or a more advanced lesion the authors recommend complementary treatment with radical surgery and/or CMT.…”
Section: Early Rectal Cancersmentioning
confidence: 87%
“…[38][39][40][41] Because of the necessity of having specific instruments and also the particular technical aspects, this method demands good training for the obtention of satisfactory results. [42][43][44] It was described that in 11 tumors located up to 4 cm of the anorectal line, a surgical conversion was necessary because of technical difficulties. 45 Due to two important disadvantages: first the high costs, taking into account the limitation of the equipment use and second, technical difficulties to perform the technique with ability and efficiency, the procedure has not achieved wide acceptance and popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these techniques demand experience and, in consequence, must be performed in reference centers where a larger number of patients are available, facing that the surgeon training is mandatory and the small frequency of the indications is a reality [41][42][43][44]. Because of the necessity of having specific instruments and also the particular technical aspects, this method demands good training for the obtention of satisfactory results [45][46][47]. It was described that in 11 tumors located up to 4 cm of the anorectal line, a surgical conversion was necessary because of technical difficulties [48].…”
Section: Discussionmentioning
confidence: 99%